Lesion Topography and Its Correlation With Etiology in Medullary Infarction: Analysis From a Multi-Center Stroke Study in China - Hong, Yue-hui; Zhou, Li-xin; Yao, Ming; Zhu, Yi-cheng; Cui, Li-ying; Ni, Jun; Peng, Bin (Frontiers in Neurology, 2018)
Background and purposes: The lesion topography of medullary infarction (MI) is heterogeneous and its correlation with stroke etiology remains elusive. We aim to clarify the lesion pattern of MI and to assess its correlation with stroke etiology. Methods: Of 1129 subjects with available DWI in SMART study (a multi-center trial concerning secondary stroke prevention in China) between April 2008 and December 2010, 43 patients with DWI confirmed MI (3.8%) were retrospectively evaluated. Lesions were categorized as lateral and medial medullary infarction (LMI and MMI, 33 and 10 subjects respectively) at 3 levels rostro-caudally and correlated with the stroke etiology. Clinical profiles and long-term prognosis were analyzed. Results: Large artery atherosclerosis, small artery disease, cardiogenic embolism and artery dissection accounted for 29, 11, 1 and 2 infarcts respectively. Large artery disease was the most common cause in LMI (24 of 33, 72.7%) whereas small artery disease was not uncommon in MMI (5 of 10, 50.0%). Though the difference of infarct pattern between large artery atherosclerosis and small artery disease was insignificant, two distinct lesion patterns were considered to be relevant: (1) Rostral MMI with continuous medial pontine infarctions were more likely attributed to small artery disease than large artery atherosclerosis. (2) Ventral MMI with dorsal extension were more often caused by large artery disease than small artery disease. During a median follow-up of 17 months, 2 patients died and 2 experienced recurrent ischemic events, 39 of 41 subjects (95.1%) were functional independent (mRS 0-2). Conclusions: This multi-center study demonstrates that MI has distinct lesion pattern depending on various stroke etiologies and mechanisms. Future investigations with larger sample size should establish the lesion pattern of MI and validate its correlation with the stroke etiology and mechanisms, which might improve stroke management.